Increased risk of SARS-CoV-2 infection and COVID-19 death among older patients at long-term care hospitals in Korea - Seon, Jeong-Yeon; Kim, Sunjea; Lim, Min Kyoung; Oh, In-Hwan (Frontiers in Public Health, 2023)
Introduction Long-term care hospitals are known to be vulnerable to SARS-CoV-2 infection and death given their numerous older chronic disease patients. However, the actual effect of long-term care hospital admission is not well known in Korea; hence, this study sought to analyze the effect of long-term care hospitalization on SARS-CoV-2 infection and COVID-19 death by correcting for patients’ characteristics. Methods This cross-sectional study used the data from K-COV-N cohort, which is linked to the National Health Insurance Service and the Korea Disease Control and Prevention Agency; it analyzed 70,373 individuals aged ≥60 years, who had been tested for COVID-19 between January 1 and May 30, 2020 (KDCA-NHIS-2020-1-601). Patients admitted to a long-term care hospital were defined as those with a confirmed history of hospitalization within 30 days of the COVID-19 testing date. The final data analysis was performed in December 2022. Logistic regression analysis of the national data was employed to determine the association between long-term care hospital admission, the risk of SARS-CoV-2 infection, and death from COVID-19. The odds ratios for SARS-CoV-2 infection and death from COVID-19 were calculated by adjusting for sex, age, residential area, health insurance premium, disability, and the Charlson Comorbidity Index. Results Older patients at long-term care hospitals had a high risk of SARS-CoV-2 infection (OR:2.91, 95% CI:2.33–3.64) and death from COVID-19 (OR:3.58, 95% CI:2.13–6.02). A difference in SARS-CoV-2 infection risk was observed based on residential area, health insurance premium (economic level), and disability; no difference was observed for COVID-19 mortality risk. Discussion Admission to a long-term care hospital itself could be a risk factor for SARS-CoV-2 infection and the consequent high mortality risk after adjusting for sex, age, disability, and comorbidities. Patients are at high risk of infection through contact with workers, leading to death; therefore, quarantine policies for workers must be strengthened.